Consolidation of Electrical Service Guidelines to Accelerate Fleet Electrification and Green Supply Chain in California - Chandra, Subhash; Patro, Ravindra Kumar (ExcelingTech, 2025)
The transition to clean and green energy is inevitable just like the changes in global climate, the former being the consequence of the latter. Time is of essence here. The U.S. Government is also pushing the speedier adoption of electric vehicles (EVs) all across the country to handle the menace of emission. Urged by ambitious policies and propelled by generous investments in clean energy, California is leading the way to fleet electrification. The accelerated electrification of fleet in California, demands consolidation of electrical service guidelines, an important impediment to speedier transition. Replacement of fleet vehicles with similar vehicles that are significantly low on emission mark an important milestone for meeting the stringent emission targets set by the state. Though local in implementation, this program has global ramifications due to its capacity to aid other regions transition to vehicle electrification to meet such worldwide emission targets, as commitments made under the Paris Climate Agreement. This article identifies the obstacles to fleet electrification and recommends ways to consolidate electrical service guideline that can expedite the fleet electrification in California, a state that is a leader in green logistics, and hence promote green supply chain.